Social Insurance and Retirement: A Cross-Country Perspective - Tobias Laun; Johanna Wallenius (Luxembourg Income Study (LIS), 2016)
We study the role of old-age pensions, disability insurance and healthcare in accounting for the differing labor supply patterns of older individuals across countries. We develop a life cycle model of labor supply and health with heterogeneous agents. In our framework, people choose when to stop working and when/if to apply for disability and pension benefits. We find that the incentives faced by older workers differ hugely across countries. In fact, based solely on differences in social insurance programs, the model predicts even more cross-country variation in the employment rates of people aged 55-69 than we observe in the data.
Keywords: E24; J22; J26; 330; Life cycle; Retirement; Disability insurance; Health